The Effect of Green Product and Price on Brand Image and Buying Interest of Gesits Electric Motorcycle in Pekanbaru City - Alhadi, Hafizh; Jushermi, Jushermi; Rahayu, Deny Danar (Westscience Press, 2025)
This study aims to examine the influence of Green Product on Purchase Intention of Gesits electric motorcycles in Pekanbaru, with Brand Image as an intervening variable. The population of this research consists of residents of Pekanbaru City who are aware of the Gesits electric motorcycle brand but have never purchased one. Sampling was conducted using non-probability sampling techniques with the Lemeshow formula, resulting in a sample size of 100 respondents. The data analysis method employed Partial Least Square-Structural Equation Modeling (PLS-SEM) using SmartPLS software version 4.1.1.1. The results indicate that Green Product has no direct or indirect effect (through Brand Image) on Purchase Intention. However, Green Product significantly influences Brand Image. Meanwhile, Price has a direct effect on Purchase Intention and Brand Image but does not indirectly influence Purchase Intention (through Brand Image). Brand Image itself does not significantly affect Purchase Intention. These findings provide strategic implications for Gesits in formulating marketing strategies, particularly in strengthening brand positioning through Green Product and Price aspects, even though Brand Image has not yet been a determining factor for Purchase Intention. This study emphasizes the importance of a holistic approach in developing effective marketing strategies for Gesits electric motorcycles.